2005
DOI: 10.1007/s11177-005-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

Grain Protein Content in Wheat: Genetics of the Character and Some Predictions for Its Improvement in Common Wheat

Abstract: The results of studies on genetic control of the grain protein content in common wheat and the attempts of its improvement using traditional breeding approaches and methods of experimental mutagenesis and introgressive hybridization are presented. The evolution of the views on the genetic structure of the character is considered. Possible explanations are given to the fact that the attempts to significantly improve the character in question in common wheat cultivars have failed in spite of long-term genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Even in early studies of aneuploides and chromo some substitution lines [24,104,105,106] it was shown on that the GPC trait can be influenced by not only structural genes identified in different chromo somes but also by regulatory genes [107]. Using ditelo somic cultivar Chinese Spring Wanous et al [108] demonstrated that 79 of 164 assumed regulatory genes (48%) show a significant effect on the expression of genes encoding high molecular glutenins (excluding dose effects of structural genes).…”
Section: Regulatory Genesmentioning
confidence: 99%
“…Even in early studies of aneuploides and chromo some substitution lines [24,104,105,106] it was shown on that the GPC trait can be influenced by not only structural genes identified in different chromo somes but also by regulatory genes [107]. Using ditelo somic cultivar Chinese Spring Wanous et al [108] demonstrated that 79 of 164 assumed regulatory genes (48%) show a significant effect on the expression of genes encoding high molecular glutenins (excluding dose effects of structural genes).…”
Section: Regulatory Genesmentioning
confidence: 99%
“…Grain protein has a significant influence on processing quality, such as dough rheological properties, baking quality, and endproduct attributes (Buck et al, 2007). The level of global protein yield in wheat has remained relatively stable, despite an increase in productivity of this crop (Zlatska, 2005). Wheat quality improvement is a major challenge for many breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable success in the genetic improvement of grain yield of common wheat varieties over the past 50 years was not accompanied with comparable progress in grain quality (Van Lill and Purchase, 1995). According to Zlatska (2005) grain protein content in wheat was among the characters that suffered from intense selection, the narrow genetic base of germplasm in use has been considered the main reason. Knowledge of genetic diversity patterns allows plant breeders to better understand the evolutionary relationships among accessions, to sample germplasm in more systematic fashions, and develop strategies that incorporate useful diversity in their breeding programs (Bretting and Widrlechner, 1995) .Information about genetic diversity and relatedness in the available germplasm and among elite breeding material is a fundamental element in plant breeding.…”
Section: Introductionmentioning
confidence: 99%